Zinc molybdate with triclinic crystal structure as antimicrobial agent

JP2025032171APending Publication Date: 2025-03-11AMISTEC GMBH & CO KG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024207367
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-10-26
Filing Date
2024-11-28
Publication Date
2025-03-11

AI Technical Summary

Benefits of technology

【0005】 その抗微生物効果が専門的分野において既に記載されているモリブデン酸亜鉛は、通常は正方晶結晶構造を有する。これは水に不溶性であり、したがって事実上無毒性である。しかし、本発明では、驚くべきことに、モリブデン酸亜鉛は、既知の正方晶結晶構造に加えて三斜晶結晶構造の安定な様式で存在することもでき、この形態が他の結晶形におけるものよりも有意に高い抗微生物有効性を示すことが見出された。この効果は、同じ粒径を有する正方晶モリブデン酸亜鉛のものと比較して有意に改善されている。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025032171000001
    Figure 2025032171000001
  • Figure 2025032171000002
    Figure 2025032171000002
Patent Text Reader

Abstract

To provide an antimicrobial agent having improved activity using molybdate.SOLUTION: The use of zinc molybdate (ZnMoO4) as an antimicrobial agent is provided. wherein the ZnMoO4 is in the form of a particle having a triclinic crystal structure and an average particle size of 0.1 μm to 5.0 μm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the use of the triclinic form of zinc molybdate (ZnMoO4) as an antimicrobial agent, to composite materials containing such zinc molybdate, and to methods of making the same. [Background technology]

[0002] Surfaces of objects are treated with antimicrobial agents or endowed with antimicrobial properties to prevent the accumulation of microorganisms. Among others, disinfectants or biocides are used to combat microorganisms. However, a major disadvantage of using organic biocides is the occurrence of resistance and cross-resistance between microorganisms. Therefore, alternative methods to effectively combat microorganisms and prevent their colonization on surfaces are increasingly being sought. One possibility is the use of metals and metal compounds. Silver and copper are particularly frequently used due to their good antimicrobial effect. In the first variant, in order to achieve a high level of activity, elemental metals are provided in a form with the largest possible surface area. In particular, nanoparticles, metal foams or nanoparticles fixed on a carrier are generally considered. The second variant provides for the provision of soluble metal salts, which are, for example, incorporated directly into zeolites or into composite materials. However, the mentioned noble metals or noble metal ions are relatively expensive and, moreover, disadvantageously, are almost completely inactivated by sulfur-containing compounds or high electrolyte concentrations.

[0003] In recent years, the use of molybdates and tungstates as antimicrobial agents has also been discussed. These compounds are relatively inexpensive and are virtually insoluble in water, making them non-toxic. However, the antimicrobial efficacy of molybdates and tungstates investigated to date is often inadequate. Summary of the Invention [Problem to be solved by the invention]

[0004] It is therefore an object of the present invention to provide antimicrobial agents with improved activity and inexpensive methods of effectively protecting materials and surfaces against microbial colonization. [Means for solving the problem]

[0005] Zinc molybdate, whose antimicrobial effect has already been described in the technical field, usually has a tetragonal crystal structure. It is insoluble in water and therefore practically non-toxic.However, in the present invention, it has surprisingly been found that zinc molybdate can also exist in a stable manner of triclinic crystal structure in addition to the known tetragonal crystal structure, and this form shows significantly higher antimicrobial effectiveness than that in other crystal forms.This effect is significantly improved compared to that of tetragonal zinc molybdate with the same particle size.

[0006] Triclinic zinc molybdate can be obtained by ultrasonically assisted reaction of a solution of one or more water-soluble molybdate salts with a solution of one or more water-soluble zinc(II) salts. In the presence of ultrasound, the water-insoluble zinc molybdate formed during the reaction of the educt salt precipitates in the form of triclinic crystals. Depending on the duration of the reaction and ultrasonic treatment, the particle size of the triclinic crystals may vary.

[0007] In accordance with the present invention, particularly good antimicrobial efficacy has been found for zinc molybdate in the form of particles having a triclinic crystal structure and an average particle size in the range of 0.10 μm to 5.0 μm, preferably 0.25 μm to 5.0 μm.

[0008] Thus, a first aspect of the invention relates to the use of zinc molybdate as an antimicrobial agent, ZnMoO4 in the form of particles having a triclinic crystal structure and an average particle size of 0.1 μm to 5.0 μm, preferably 0.25 μm to 5.0 μm. According to a further embodiment, the use of triclinic ZnMoO4 with an average particle size in the submicron range, i.e. from 0.1 μm to less than 1.0 μm, is preferred.

[0009] Triclinic zinc molybdate is non-toxic to humans and animals and therefore has excellent biocompatibility. It can be produced relatively inexpensively and exhibits strong antimicrobial effects even in small amounts. Furthermore, zinc molybdate is not inactivated by sulfur-containing compounds or high concentrations of electrolytes, but rather retains its effectiveness.

[0010] Zinc molybdate having a triclinic crystal structure and the above-mentioned particle size exhibits high antimicrobial activity against a broad range of microorganisms, including algae, fungi, and viruses, as well as gram-positive and gram-negative microorganisms, regardless of their antibiotic resistance. Examples of microorganisms against which the triclinic zinc molybdate according to the invention is effective include, inter alia, Lactobacillus acidophilus, Pseudomonas such as P. aeruginosa, Salmonella such as S. aureus, E. coli, Candida species such as C. albicans, C. glabrata, and C. tropicalis, Legionella, Listeria fungi; viruses such as influenza, Epstein-Barr virus, rotavirus, and norovirus; and Aspergillus niger, Aspergillus fumigatus, and Aspergillus flavus. At the same particle size, the antimicrobial effect is significantly higher than that of zinc molybdate having a different crystal structure. In a preferred embodiment of the present invention, the zinc molybdate according to the present invention is particularly effective against algae growth.

[0011] The particle size of ZnMoO4 is preferably in the range of 0.10-2.5 μm, more preferably in the range of 0.15-2.5 μm, more preferably in the range of 0.2 μm to less than 1.0 μm. Particles smaller than 0.10 μm, especially nanoparticles, are not provided by the present invention. Excellent antimicrobial efficacy is achieved with the triclinic crystal structure of zinc molybdate with an average particle size in the micrometer range, thereby avoiding the risks associated with nanoparticles. Zinc molybdate with a triclinic crystal structure is particularly effective in the submicron range.

[0012] Triclinic zinc molybdate itself is insoluble in water. When in contact with water or air humidity, zinc molybdate causes a drop in the pH value. Zinc molybdate itself does not go into solution and will not decompose or leach from the material.

[0013] For antimicrobial use, triclinic zinc molybdate can be used alone or in combination with other active ingredients and / or adjuvants. In a particularly preferred embodiment, triclinic zinc molybdate is combined with molybdenum oxide MoO3, which allows the antimicrobial efficacy to be further improved. MoO3 can in principle have any desired crystal structure, for example orthorhombic or monoclinic. MoO3 with orthorhombic crystal structure has proven to be particularly advantageous according to the present invention. Triclinic ZnMoO4 and MoO3 can be present in the form of a crystal mixture or as a mixed crystal. The use of a mixture or mixed crystal of triclinic ZnMoO4 and orthorhombic MoO3 is particularly preferred.

[0014] Further advantages arise when triclinic zinc molybdate is used in combination with at least one hydrophilicising or hygroscopic agent. Particularly preferred hydrophilising and hygroscopic agents are described below.

[0015] According to the present invention, triclinic zinc molybdate can be incorporated into or at least deposited on the surface of a material that provides antimicrobial properties, resulting in an antimicrobial composite material.

[0016] The present invention therefore also relates to an antimicrobially active composite material comprising ZnMoO4 in the form of particles having a triclinic crystal structure and an average particle size in the range of 0.1 μm to 5.0 μm, more preferably 0.20 μm to 5.0 μm, more preferably 0.25 μm to 5.0 μm, more preferably 0.50 μm to 2.5 μm, even more preferably 0.70 μm to 1.5 μm. According to one embodiment, the use in the composite material of triclinic ZnMoO4 with an average particle size in the submicron range, i.e. from 0.1 μm to less than 1.0 μm, is preferred.

[0017] In the context of the present invention, a composite material is understood to mean a material consisting of two or more materials connected to one another, at least one of which is triclinic zinc molybdate as defined above. The further material can in principle be formed from any material and can also be, for example, a composite material itself.

[0018] The presence of triclinic zinc molybdate gives the composite material according to the invention an antimicrobial effect. The adhesion of pathogenic pathogenic bacteria is greatly reduced. The growth of microorganisms and the formation of biofilms are inhibited. This is particularly important, for example, in hospitals, nursing homes, etc., since the microorganisms in the biofilm cannot be eliminated, or at least not permanently, by antibiotics, organic biocides, disinfectants, etc. A reduction in the pH value is only necessary in the region of the surface boundary layer of the composite material or component or product made therefrom, so that a correspondingly small amount of zinc molybdate in the region of the surface is sufficient to achieve the desired antimicrobial effectiveness.

[0019] In a preferred embodiment, the adhesion of algae and / or biofilms to the surface is reduced. Thus, the use of zinc molybdate according to the invention to prevent fouling, i.e. the unwanted colonization of organisms on industrial surfaces such as ship hulls, represents a preferred embodiment of the invention.

[0020] Since triclinic zinc molybdate is practically insoluble in water, it does not wash out of the composite material, but remains there, and its antimicrobial effectiveness is maintained throughout the useful life of the composite material. In this context, it has surprisingly been found that triclinic zinc molybdate is retained in the material even better than zinc molybdate with a different crystal structure.

[0021] At least one further material of the composite material can in principle be selected from any material class. For example, the material can be an inorganic, metallic, ceramic or organic material, or any combination thereof. Other possible materials are, for example, plastics, paints, lacquers, silicones, rubbers, melamines, acrylates, methyl acrylates, waxes, epoxy resins, glass, metals, ceramics, etc. In a preferred embodiment, the composite material according to the invention comprises at least one organic polymer or compound and / or silicone as further material. The material in or on which triclinic zinc molybdate is introduced for the purpose of antimicrobial finishing can form a solid and / or liquid matrix. It can be provided that triclinic zinc molybdate is added so that it constitutes 0.1% to 10% (weight percent or volume percent) of the total weight or volume.

[0022] Composite materials can in principle be designed as layered, fiber, particulate or interpenetrating composites.

[0023] In principle, the composite material according to the present invention can be solid or liquid under standard conditions. For example, the composite material can be in the form of a solution, suspension, and / or dispersion, for example as a lacquer or liquid coating. The use of zinc molybdate according to the present invention as a lacquer or liquid coating is preferred. The lacquer or coating according to the present invention can be applied to any suitable surface, such as plastic, metal, wood, stone, and other building materials. In such a case, the composite material becomes hard after curing.

[0024] Triclinic zinc molybdate can be arranged on the surface of the composite material and / or distributed in the composite material. According to the present invention, the arrangement of triclinic zinc molybdate in the area of ​​the surface of the composite material is preferred because antimicrobial effect is desired here. For example, zinc molybdate can be applied to a substrate or carrier material as a layer or as a component of a layer. In principle, only one or more areas of the surface of the composite material or the entire surface can be antimicrobially finished with triclinic zinc molybdate. Alternatively or additionally, triclinic zinc molybdate can also be arranged or distributed in the composite material. This ensures that the antimicrobial effect is permanently retained even when the surface of the composite material is worn.

[0025] Depending on the intended use, the composite material in the context of the present invention can in principle exist as a semi-finished product, i.e. as a semi-finished material that reaches its final use form only after further processing steps, or the composite material can already be designed as a finished component that can be used for its desired purpose without further processing steps.

[0026] The composite material according to the invention can contain triclinic zinc molybdate alone or in combination with other active ingredients and / or adjuvants. In a particularly preferred embodiment, triclinic zinc molybdate is combined with molybdenum oxide MoO3, which allows the antimicrobial efficacy to be further improved. MoO3 can in principle have any desired crystal structure, for example orthorhombic or monoclinic. MoO3 with an orthorhombic crystal structure has proven to be particularly advantageous according to the invention. Triclinic ZnMoO4 and MoO3 can be present in the form of a crystal mixture or as a mixed crystal. The use of a mixture or mixed crystal of triclinic ZnMoO4 and orthorhombic MoO3 is particularly preferred.

[0027] In a preferred embodiment, the composite material according to the invention, in addition to triclinic ZnMoO4 and possibly MoO3, does not have antimicrobial compounds such as silver or silver compounds, in particular soluble silver compounds such as nanosilver or silver nitrate. Also, copper, organic biocides, zeolites, etc. are preferably not contained in the composite material according to the invention. In this way, better environmental compatibility and a considerable cost reduction are achieved.

[0028] The mass content of triclinic zinc molybdate, based on the total mass of the composite material, is advantageously 0.1-80% by weight, in particular 1.5-30% by weight, preferably 1.8-5.0% by weight. At this mass ratio, a particularly high antimicrobial effectiveness is ensured with the lowest possible use of zinc molybdate.

[0029] The use of particles with the aforementioned average particle size offers the unique advantage that, on the one hand, a particularly high antimicrobial effectiveness can be achieved, and, on the other hand, the composite material according to the invention does not contain nanoparticles.Furthermore, the introduction of ZnMoO4 with the particle size according to the invention does not result in any clouding of the correspondingly doped composite material.Transparent lacquers remain transparent even after the introduction of ZnMoO4 according to the invention.

[0030] Further advantages result when triclinic zinc molybdate is used in combination with at least one hydrophilizing or hygroscopic agent, which is at least located in the surface region of the composite material. In this way, the antimicrobial effectiveness is significantly increased, especially in dry environments, i.e., for example, environments with very low air humidity and a correspondingly small amount of available water, which are important for the formation of an acidic surface boundary layer. Examples of suitable hydrophilizing and / or hygroscopic agents are, in particular, SiO2, especially in the form of silica gel or as pyrogenic silicon dioxide. These form a kind of moisture buffer and thus ensure a minimum level of moisture in the product. Furthermore, it has been found that the association of triclinic zinc molybdate with SiO2 has the effect that triclinic zinc molybdate is particularly well retained in the composite material, and runoff can be completely prevented. SiO2 is preferably used with a particle size distribution in the range of an average particle size of 0.25 μm to 25 μm.

[0031] Further examples of other hydrophilizing and / or hygroscopic agents which can be used according to the invention are organic acids such as abietic acid, arachidonic acid, arachidic acid, behenic acid, capric acid, caproic acid, cerotic acid, erucic acid, fusaric acid, fumaric acid, bile acid, icosenoic acid, isophthalic acid, lactonic acid, laurinic acid, lignoceric acid, linoleic acid, levopimaric acid, linoleic acid, margaric acid, melissic acid, montanic acid, myristic acid, neoabietic acid, nervonic acid, nonadecanoic acid, oleic acid, palmitic acid, palmitoleic acid, pelargonic acid (nonanoic acid), pimaric acid, palustric acid, palmitic acid, ricinoleic acid, stearic acid, sorbic acid, tannic acid, tridecanoic acid, undecanoic acid, and vulpic acid. Furthermore, malonic acid, maleic acid and maleic anhydride, lactic acid, acetic acid, citric acid, salicylic acid, and ascorbic acid, as well as their salts, have proven advantageous. Acid anhydrides, ampholytes, buffer systems, polymeric acids, ion exchange resins, as well as acid sulfonates and acid halides can also be used.

[0032] The mass content of the hydrophilizing agent and / or moisture absorbing agent, based on the total weight of the complex, is advantageously in the range of 0.1% to 15%. For example, the mass content can be 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, or 14%. Mass contents in the range of 1 to 5%, preferably in the range of 2 to 4%, are particularly advantageous. Furthermore, the mass contents or mass ratios of the hydrophilizing agent and / or moisture absorbing agent can be set to correspond to the mass content of the selected triclinic zinc molybdate.

[0033] In a particularly preferred embodiment, the triclinic zinc molybdate is at least partially coated with and / or co-aggregated with a hydrophilizing and / or hygroscopic agent, in particular SiO2. This ensures in a simple manner the spatial proximity of the two classes of compounds, so that the zinc molybdate is readily supplied with the moisture required to lower the pH value, even under particularly dry conditions.

[0034] In a further aspect of the present invention there is provided the use of an antimicrobially active composite material as defined above for producing an antimicrobially active product.

[0035] Another aspect of the present invention relates to a method for producing an antimicrobially active composite material as defined above, for which purpose zinc molybdate is preferably provided in the form of particles having an average particle size in the range of 0.10-5.0 μm, more preferably 0.15 μm to less than 1.0 μm, more preferably 0.20 μm to less than 1.0 μm, even more preferably 0.25 μm to less than 1.0 μm, combined with at least one further material.

[0036] Triclinic zinc molybdate can be produced by ultrasonically assisted reaction of one or more water-soluble molybdates with one or more water-soluble zinc(II) salts. For this purpose, aqueous solutions of molybdate and zinc salt are prepared separately from each other and brought into contact with the action of ultrasound. The presence of ultrasound causes zinc molybdate to crystallize in a triclinic crystal structure. The particle size of zinc molybdate can be adjusted by the duration and intensity of ultrasound. In a preferred embodiment of the invention, triclinic zinc molybdate is produced by contacting an aqueous solution of one or more alkali or alkaline earth molybdates with an aqueous solution of one or more zinc(II) salts. For example, sodium molybdate dihydrate can be used as water-soluble zinc molybdate. A zinc halide, such as zinc chloride, can be used as a zinc(II) salt. The two salt solutions are reacted, preferably at room temperature and in the presence of ultrasound, at frequencies higher than 15 kHz, in particular 20-30 kHz. For the best possible effectiveness, zinc molybdate must be present in a crystal lattice as free of defects as possible. This is ensured by ultrasonic treatment. A mixture of reactants as a water-soluble molybdate salt and one or more water-soluble zinc salts without energy input will not result in the formation of an optimal crystal structure, which is manifested by a lack of effectiveness or reduced effectiveness compared to the optimal crystal structure according to the present invention.

[0037] The ultrasonic production of triclinic ZnMnO4 also allows in particular a defined provision of particles in the submicron range, ie greater than 0.1 μm and smaller than 1 μm in the context of the present invention.

[0038] In the production of the composite material, triclinic zinc molybdate is advantageously combined with at least one hydrophilizing agent and / or moisture absorbing agent as defined above, the latter being located at least in the region of the surface of the composite material. It has proven particularly advantageous to at least partially coat and / or agglomerate the zinc molybdate with the hydrophilizing agent and / or moisture absorbing agent, in particular SiO2.

[0039] The lack of water solubility of zinc molybdate according to the present invention is demonstrated in a wipe test.After the melamine resin sample containing zinc molybdate according to the present invention is wiped with water-alcohol mixture 10,000 times, neither zinc molybdate nor zinc nor molybdenum can be detected in the wipe fabric.On the other hand, the antimicrobial effect of the corresponding melamine resin sample remains unchanged.

[0040] The invention is further illustrated with the following figures and examples. [Brief description of the drawings]

[0041] [Figure 1] Figure 1. Antimicrobial effectiveness of different crystalline forms of zinc molybdate: 1) monoclinic ZnMoO4 vs. orthorhombic MoO3, 2) triclinic ZnMoO4 vs. orthorhombic MoO3, 3) monoclinic ZnMoO4 vs. amorphous MoO3. Triclinic zinc molybdate is clearly superior to the other crystalline forms, showing that the tested samples were completely sterile after only 6 hours.

[0042] Efficacy tests were performed with three ATCC reference pathogens (Staphylococcus aureus ATCC25923, Escherichia coli ATCC25022, and Pseudomonas aeruginosa ATCC15442). All pathogens listed were susceptible. No resistant pathogens were found. Lactobacillus acidophilus (acid resistant) was also eradicated.

[0043] [Diagram 2] Figure 1 shows the antimicrobial effectiveness of two different SiO2 coatings on a hospital table (Coating I and Coating II) containing zinc molybdate with a particle size of 0.2 μm against Staphylococcus aureus. The coating containing zinc molybdate according to the invention shows a significant reduction after 1 and 3 hours and complete sterility after 6 hours.

Claims

1. ZnMnO 4 Zinc molybdate (ZnMoO) as an antimicrobial agent, 4 ) use.

2. ZnMoO 4 2. Use according to claim 1, wherein the average particle size is in the range of 0.15 μm to less than 1.0 μm, preferably in the range of 0.20 μm to less than 1.0 μm.

3. ZnMoO 4 MoO 3 , preferably orthorhombic MoO 3 3. The use according to claim 1 or claim 2 in combination with

4. ZnMoO in the form of particles having a triclinic crystal structure and an average particle size of 0.1 μm to 5.0 μm 4 and at least one further material.

5. The triclinic ZnMoO 4 MoO, preferably having an orthorhombic crystal structure, present in a mixture with 3 5. The antimicrobial composite material of claim 4, further comprising:

6. 6. The antimicrobial composite material according to claim 4 or claim 5, further comprising at least one hydrophilizing agent and / or moisture absorbing agent disposed at least in a region of the surface of the composite material.

7. The ZnMoO 4 is at least partially coated with and / or coagulated with said hydrophilizing agent and / or moisture absorbing agent.

8. The hydrophilizing agent and / or moisture absorbing agent is SiO 2 8. A composite material according to claim 6 or claim 7, which comprises a pyrogenic silica, in particular a silica gel or a pyrogenic silicon dioxide.

9. ZnMoO based on the total mass of the composite 4 9. The composite material according to claim 4, wherein the mass content of is between 0.1% and 80%, in particular between 1.5% and 30%, preferably between 1.8% and 5.0%.

10. 10. A composite material according to any one of claims 3 to 9, characterized in that the further material comprises at least one organic polymer and / or silicone.

11. 11. Composite material according to any one of claims 3 to 10, characterized in that it is designed as a layer composite, a fiber composite, a particle composite or a through composite.

12. Use of an antimicrobially active composite material according to any one of claims 3 to 11 for the production of an antimicrobially active product.

13. ZnMoO in the form of particles having an average particle size of 0.20 μm to 5.0 μm, preferably 0.25 μm to 5.0 μm 4 12. A method for producing an antimicrobially active composite material according to any one of claims 3 to 11, characterized in that it comprises combining with at least one further material.

14. The ZnMoO 4 14. The method of claim 13, wherein the compound is produced by ultrasonically assisted reaction of one or more water-soluble molybdates with one or more zinc(II) salts in an aqueous solution.

15. 17. The method according to claim 16, characterized in that an aqueous solution of sodium molybdate dihydrate is reacted at room temperature with an aqueous solution of zinc chloride by the action of ultrasound at frequencies higher than 15 kHz, in particular between 20 and 30 kHz.

16. 16. The method according to any of claims 13 to 15, characterized in that at least one hydrophilizing agent and / or moisture absorbing agent is arranged at least in a region of the surface of the composite material.

17. ZnMoO 4 is at least partially coated with and / or coagulated with said hydrophilizing agent and / or moisture absorbing agent.